Anesthetics and high-pressure interaction upon elastic properties of a polymer membrane. - Kamaya, H (1981)
Anesthetics expand cell membranes, and high pressures (about 10-15 MPa) antagonize the anesthetic action. It is also known that inhalation anesthetics expand elastomer membranes. The mechanism of pressure antagonism of anesthetic action on membrane expansion was investigated in the present study with Silastic membranes. Halothane increased the length of Silastic membrane (0.14% per kPa), with an accompanying decrease of Young's modulus (3.7.10(5) Newton/m2 per kPa). High pressure decreased the length of the membrane and increased Young's modulus. The magnitudes of the pressure effect on the length and Young's modulus of the Silastic membrane in the presence of the anesthetic were not identical with those observed in the absence of the anesthetic. In the presence of halothane at pressures common to clinical applications, the bulk modulus of the membrane decreased about 4.6-4.0%. These results suggest that the effects of pressure and anesthetic upon the elastomer may not be completely independent of each other.